An exploration of factors that mediate the relationship between adverse childhood experiences and sexual assault victimization among LGBTQ+ college students - Sutton, Tara E. (Child maltreatment, 2022)
Despite alarming rates of sexual assault on college campuses, little research has examined risk factors for sexual victimization among LGBTQ+ college students. This exploratory study aims to examine adolescent sexual assault, internalized homonegativity, and problematic alcohol use as mediators linking several types of adverse childhood experiences (ACEs; i.e., childhood sexual abuse, parental abuse, and household disorder) to collegiate sexual assault. Utilizing data from 241 LGBTQ+ college students, path analysis findings demonstrated that these proposed mediators increased risk for sexual assault and that various types of ACEs exerted differential impacts on sexual re-victimization, internalized homonegativity, and problematic alcohol use. Practice-based implications are offered, including the need for affirming programming that includes problem drinking prevention components and considers the role of ACEs and internalized homonegativity in increasing risk for sexual assault during college as well as the need for LGBTQ+ resource centers on campus.